Tingkat Kecemasan pada Lansia yang Dilakukan Terapi Teknik Relaksasi Otot Progresif dan Terapi Reminiscence - Adawiyah, Siti Robeatul; Anwar, Syamsul; Nurhayati, Nurhayati (Jurnal Kesehatan, 2022)
Anxiety experienced by the elderly in Indonesia is very high. Anxiety disorders in the elderly reach 5.5%, which is often experienced by those aged 60 years and over. The purpose of this study was to determine the effect of progressive muscle relaxation techniques and reminiscence therapy on the level of anxiety in the elderly. This research is a quasi-experimental study, with a total sampling technique of 30 respondents who were divided into 2 groups. The instrument in this study used HARS. Data analysis using paired samples test and GLM. The results showed a decrease in anxiety levels after the intervention with p-value=0.000. The results obtained in these two interventions were a p-value of 0.000<0.05, it can be concluded that there was a change in the value of decreasing anxiety in the elderly before and after the progressive muscle relaxation technique and reminiscence therapy was carried out. Suggestions for further researchers need to do similar research with the addition of a larger number of respondents. Therefore, intervention was carried out not in groups, and different sample criteria were carried out to get maximum results.